The smooth muscle cell membrane during atherogenesis: A potential target for amlodipine in atheroprotection - Tulenko, T.N.; Sumner, A.E.; Chen, M.; Huang, Y.; Laury-Kleintop, L.; Ferdinand, F.D. (The American heart journal, 2001)
Background Atherosclerotic disease has been present in the human population apparently from the beginning of time. However, it has only been in the 20th century that improvements in the control of infectious diseases have allowed the average life span to increase to the point where atherosclerosis has been able to affect the general population. By the middle of the 20th century, atherosclerosis had reached epidemic levels, and it is currently pandemic and increasing worldwide. Despite its growing significance to health care, we still know relatively little about the cellular basis for plaque genesis in the vessel wall. Current thinking holds that atherosclerosis is caused by an unchecked chronic inflammatory process involving the cells of the arterial wall and their interaction with LDL and various inflammatory cells. Considerable evidence suggests that the principal insults underlying atherogenesis are serum dyslipidemias and oxidative stress mediated primarily by oxidized LDL. However, just how these insults alter the cell biology of vascular cells and lead to the atherosclerotic phenotype is still under intense investigation. Moreover, recent clinical trials have provided evidence that certain classes of drugs, including newer calcium channel blockers (CCBs), can remodel the arterial smooth muscle cell (SMC) membrane and inhibit the progression of atherosclerotic disease. Methods This review summarizes our current thinking on atherogenesis in the arterial SMC and considers recent developments regarding alterations in the SMC membrane during the very early period of atherogenesis. We also discuss how certain CCBs might operate to produce atheroprotection. Results The SMC membrane becomes enriched in unesterified cholesterol soon after the development of serum hypercholesterolemia. With excess membrane cholesterol, the membrane becomes thicker and develops distinct cholesterol domains. These alterations in the membrane increase the permeability of SMC to calcium and induce a variety of alterations in SMC function that contribute to cellular atherogenic processes during plaque genesis. Amlodipine, a third-generation CCB, markedly inhibits the progression of lesions. The explanation of this novel action may lie in the effects of this drug on various potential cellular targets. Conclusions Evidence is accumulating that excess membrane cholesterol may contribute to the cellular defects responsible for the transformation of the SMC to the atherosclerotic phenotype. Amlodipine, which has membrane–remodeling properties, is emerging as an important atheroprotective drug. (Am Heart J 2001;141:S1-11.)